LOPP chemotherapy as a first‐line treatment for dogs with T‐cell lymphoma. (16th May 2017) - Brown, P. M.; Tzannes, S.; Nguyen, S.; White, J.; Langova, V.
Abstract : Background: The aim of this study was to describe the use of a lomustine (CCNU), vincristine, procarbazine and prednisolone (LOPP) protocol used for treatment of chemotherapy naive T‐cell lymphoma patients and to describe the response rate, toxicity and disease‐free interval compared historically to CHOP chemotherapy. Materials and Methods: Retrospective case study of 31 dogs with naïve T‐cell lymphoma treated with a lomustine (CCNU), vincristine, procarbazine and prednisolone (LOPP) protocol. Results: Thirty‐one dogs with T cell lymphoma were treated. The overall response rate was 97%. Of the 30 dogs that had a response to LOPP chemotherapy, the median disease free interval was 176 days (range 0–1745 days). The median overall survival time for this study group was 323 days (range 51–1758 days). All deaths in this study were attributable to lymphoma. Conclusion: LOPP chemotherapy for T cell lymphoma is well tolerated with a low toxicity profile and an excellent overall response rate. This protocol showed minimal toxicity and comparable disease free interval and survival times for canine high grade T cell lymphoma treated with CHOP.